The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14202/vetworld.2018.1669-1676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic Pediococcus acidilactici FT28 on growth performance, nutrient digestibility, health status, meat quality, and intestinal morphology in growing pigs

Abstract: Aim:The experiment was conducted to evaluate the effect of swine-origin probiotic Pediococcus acidilactici FT28 on growth, nutrient utilization, health status, meat quality and intestinal morphology in growing female pigs.Materials and Methods:Pigs (n=27) were distributed into three groups (3 replicates of 3 each) and supplemented with basal diet either without probiotics (C) or with a probiotic of dairy-based (Lactobacillus acidophilus NCDC-15; TLact) or swine based (P. acidilactici FT28; TPedic). The probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
(31 reference statements)
1
23
1
Order By: Relevance
“…The probiotics enhanced the animal body weight because as a natural resident, LAB is present in the guts. The pathway produces metabolites such as lactic acids and stimulates digestive enzymes and improved the digestive system (Joysowal et al, ). Moreover, the probiotic caring of cell film (membrane) against the pathogenic micro‐organisms after adhering to colonizing the epithelium of gastrointestinal tract improved the function of the immune system (Yu, Wang, Li, & Qiao, ).…”
Section: Discussionmentioning
confidence: 99%
“…The probiotics enhanced the animal body weight because as a natural resident, LAB is present in the guts. The pathway produces metabolites such as lactic acids and stimulates digestive enzymes and improved the digestive system (Joysowal et al, ). Moreover, the probiotic caring of cell film (membrane) against the pathogenic micro‐organisms after adhering to colonizing the epithelium of gastrointestinal tract improved the function of the immune system (Yu, Wang, Li, & Qiao, ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of P. acidilactici FT28 was consistent with a decreased serum TG concentration. Joysowal et al ( 60 ) also observed a lower serum TG level by supplementing species-specific P. acidilactici and L. acidophilus in grower-finisher pigs. Blood analyses showed that the fermented feed increased glucose and decreased urea concentrations, data that are indicative of alterations in metabolism associated with the diet ( 61 ).…”
Section: Resultsmentioning
confidence: 94%
“…In general, when applied as probiotics, beneficial LAB have the following positive effects in animals: prevention against colonization by (antibiotic resistant) pathogens, modulation of the intestinal microbiota, reduction of inflammatory reactions, improvement of carcass traits, modulation of the immune response, performance enhancement, increase in nutrient digestibility and absorption, and decrease in urea and ammonia excretion (Figure 1) [6,34,38,43]. Therefore, dietary probiotics not only have effects on animal health and performance, but they also have potential commercial applications, with impacts on the quality of direct products and byproducts resulting from livestock production [36,37,47].…”
Section: Lab In Livestock Productionmentioning
confidence: 99%